Fertility Decline and its Demographic Impact - Dabbagh, Firas N. (Eximia, 2024)
This paper examines the global issue of declining fertility rates and its demographic impact, focusing on Europe and Qatar as case studies. Infertility is explored both biomedically and as a social construct, influenced by societal perceptions and individual desires for parenthood. Globally, declining fertility rates pose significant challenges, particularly in developed nations facing aging populations and shrinking workforces. The paper analyzes the intricate relationship between fertility, family planning, and socio-economic development, highlighting how access to information and reproductive choices empowers women and influences family size. Factors affecting fertility, including age-related decline and delayed childbearing, are discussed. The role of gender equality in fertility transitions is emphasized, arguing that more significant gender equity within families is crucial for achieving desired fertility rates. European fertility trends, characterized by below-replacement levels, are analyzed in relation to social security systems, family support policies, and employment policies. Finally, the paper examines Qatar's demographic challenges and aspirations outlined in its National Development Strategy 3 (NDS3), which aims to increase marriage, reduce divorce, and raise fertility rates through various social and financial incentives. Thus, the paper adopts a descriptive-analytical methodology to conclude with recommendations for reform, focusing on work-life balance, family-centered policies, and individual empowerment to address declining fertility rates and promote sustainable demographic environments.